2019
DOI: 10.1111/jerd.12458
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐guided implant surgery and full‐arch immediate loading with prefabricated—metal framework—provisional prosthesis created from a 3D printed model

Abstract: Objective In this article, we describe the planning phase and clinical procedure where a CAD CAM 3D printed master model was utilized to create a prefabricated—titanium reinforced—fixed provisional prosthesis for a full‐arch immediate loading after computer‐guided implant placement. Clinical Considerations The clinical procedure should be performed based on digital planning through an advanced surgical planning software and following the guidelines of full‐arch immediate loading protocol. The fact that the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(82 reference statements)
0
16
0
2
Order By: Relevance
“…In dentistry, bone models were more frequently used for simulating dental implant placement [ 30 , 41 , 81 ]. In oral and maxillofacial surgery, the models were more frequently used for planning a bone reconstruction [ 15 – 17 , 36 , 40 , 47 , 50 , 53 , 72 ] or a tumor removal [ 18 , 49 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In dentistry, bone models were more frequently used for simulating dental implant placement [ 30 , 41 , 81 ]. In oral and maxillofacial surgery, the models were more frequently used for planning a bone reconstruction [ 15 – 17 , 36 , 40 , 47 , 50 , 53 , 72 ] or a tumor removal [ 18 , 49 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, no author did quantitative or comparative tests using models printed by VP. However most authors suggested that this technique was efficient for creating adequate models, enhancing the quality of the training [ 12 , 35 ] and suitable for planning complex surgeries [ 15 ] or dental implant treatments [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of non‐engaging conical abutments for bridge prosthesis and the application of the recommended manufacturer torque might have ensured complete seating on the implants via deformation of the prosthesis, which was noticed from resistance to the tightening of the retaining screws. Since all the prostheses were eventually seated on the implants, it can be assumed that this clinical protocol is feasible (Lanis et al., 2019; Leite et al., 2020; Schubert et al., 2019; Venezia et al., 2019). However, the study revealed that all the prostheses were associated with measurable errors in the vertical position and proximal contact regions that may have a clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is feasible to combine the sCAIS with digital prosthesis fabrication in a single workflow to immediately load the implants. In this workflow, the prosthesis is fabricated according to the digital implant planning prior to the actual implant placement (Lanis et al., 2019; Leite et al., 2020; Venezia et al., 2019). Subsequently, at the time of implant surgery, the implants are placed via sCAIS, followed by immediate restoration by the premade digital prosthesis (Johansson et al., 2009; Komiyama et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Severe bone atrophy makes doctors apply various augmentation methods, but in some clinical situations [9], it is necessary to manage only the available bone [10]. This implies the need for a thorough clinical and radiological examination of the patient in order to be able to place implants and ensure the prosthodontic restoration function [11], especially if the short implants are planned [12].…”
Section: Introductionmentioning
confidence: 99%